The evolution of exoskeleton moulting in Trilobita - Drage, H (2019)
Moulting is the process of replacing an exoskeleton. The exoskeleton provides protection but must be periodically moulted for growth, development, and repair. Moulting is therefore intrinsic to ontogeny, but is risky and energetically-expensive, meaning the morphology and behaviours of an animal are also important. Ecdysozoa (e.g. Euarthropoda, Nematoida) are united by moulting, but Euarthropoda (e.g. insects, crustaceans) have particularly tough, usually reinforced, exoskeletons. Correspondingly they have a high preservation potential and exceptional fossil record. Amongst arthropods, the extinct trilobites were extraordinarily abundant and diverse, with an unparalleled fossil record. Both trilobite carcasses and moults are abundant, and when correctly identified these moults inform on many aspects of evolutionary history. Trilobites were both extremely inter- and intraspecifically variable in their moulting compared to other euarthropods. By examining trilobite moults we can reconstruct and contrast moulting behaviours to other groups to explore the ways in which moulting has affected trilobite evolutionary history. This thesis illustrates the importance of moulting to the evolution of trilobite, and euarthropod, life history. First, I provide a review of published information on trilobite moulting, and discuss the importance of accurate moult identification. I then present a broad-scale database of trilobite behavioural and morphological data, which is used to quantitatively answer “how variable was trilobite moulting behaviour, and is this linked to differences in morphology?” Case studies then explore the detailed moulting information available from Konservat-Lagerstätten (focusing on the early Cambrian Emu Bay Shale); the association between moulting and morphology through trilobite ontogenetic history (by describing the development of Dalmanitina); and show that the process of moulting has been conserved throughout euarthropod evolution (by describing a complete moulting sequence of Symphysurus). The manuscripts constituting this thesis demonstrate the trilobite fossil record of moulting is an important source of information that can inform on the evolutionary history of development, behaviour, ecology, and morphology in this influential group.